A study of surgical site infections with and without the use of pre-operative antibiotics - Gupta, Arun Kumar; Mittal, Seema; Singh Dall, Tejinder; Bansal, Darpan (International Surgery Journal, 2019)
Background: In spite of advances in infection control, infection still remains the major limitor of surgical horizons. After urinary tract infection, surgical site infection is a main factor contributing to morbidity and mortality. Methods: The present study was carried out in the department of General Surgery and Microbiology at Shri Guru Ram Das Institute of Medical Sciences and Research, Vallah, Sri Amritsar. In this study 100 patients were selected undergoing clean or clean contaminated surgeries out of which 50 patients were not given pre-operative antibiotics (first group) and remaining 50 patients (second group) were given preoperative antibiotics. Results: Sample consisted of 100 patients with mean age of patients was 36.97 years. Total number of males was 57 and females were 43. 25 (50%) of patients who had not received prophylaxis developed SSI (group A) and 28 (56%) patients who received prophylaxis developed SSI (group B). Most common bacteria isolated from SSI was Staphylococcus aureus for both the groups. 10 (52.63%) Gram positive bacteria were isolated from microscopic examination of infected sample (A) and 25 (73.52%) were gram negative bacteria. 25 (73.52%) were Gram positive bacteria in group (b) and 9 (26.47%) were Gram negative isolates. Conclusions: It can be concluded from the present study that there is no need to give antibiotic prophylaxis prior to surgery in order to reduce the incidence of surgical site infection.